Pelatihan Metode An Nahdliyah Dalam Membaca Al- Qur’an Di TPQ Darussalam Dusun Sumbergayam Desa Kepung Kecamatan Kepung Kediri: An-nahdliyah, TPQ Darussalam, Pelatihan. - mubarok, Ahmad Sihabuddin; M. Alfin Ngainun Naima (LP3M IAIFA Kediri, 2023)
Reciting the Quran has an important role in improving the talent of forming a strong muslim personality and a solid community order. Therefore, reciting the Quran contains the essence of goodness, laughter, modesty, togetherness, social solidarity, and so on. Indeed, many of them do. Researchers will provide assistance to read the Quran with annahdliyah method to improve the quality of reading the Quran in tpq Darussalamah in Sumbergayam Hamlet, Kepung Village, Kepung District, Kediri Regency, because how to read the Quran in the community is still very lacking, because using the An-nahdliyah method using beats so many children are still in difficulty.